Certain Problems of Fighting Ecocide - GRECHENKOVA, Oksana Y. (Journal of Advanced Research in Law and Economics; Vol 8 No 3 (2017): JARLE Volume VIII Issue 3(25) Summer 2017, 2017)
A range of problems related to opposition and qualification of ecocide acts according to the Criminal Code of the RF are viewed, namely: the problem of ratio of ecocide and ecological crimes in the Russian criminal legislation; the issue of limits of qualification in case of intended infliction of death to a human; the problem of responsibility of legal entities and state for ecocide; responsibility for order on conduct of ecocide; issue of legal assessment of preparation and planning of ecocide.